Standards in the international telecommunications regime - Raymund Werle (Hamburg Institute of International Economics (HWWA), 2001)
Technical standards in telecommunications – the central focus of this paper - were traditionally developed by official government accredited or intergovernmental organizations. In the last two decades, however, private forums and consortia of standardization have evolved which initiated a shift from a predominantly technical to a business approach to standards-setting. The business perspective also guides the evaluation of standards in trade policy at the European and at the international level. In the EU and more so in the WTO regional and national diversity of standards is generally regarded as a barrier to trade. Thus harmonization of diverging standards – and not standards competition – and/or the adoption of new international standards is stipulated. Only standards adopted by official organizations are regarded as legitimate. Private organizations and the standards developed by them tend to be ignored. – – Traditionell wurden technische Standards in der Telekommunikation - dem zentralen Gegenstand dieses Papiers - von anerkannten nationalen oder intergouvernementalen Organisationen entwickelt. In den letzten beiden Jahrzehnten sind jedoch private Foren und Konsortien entstanden, die einen Wandel initiiert haben von einem technisch zu einem kommerziell geprägten Verständnis von Standardisierung. Dieses leitet auch die Beurteilung von Standards durch die Handelspolitik auf europäischer und internationaler Ebene. In der EU und mehr noch in der WTO werden regional und national unterschiedliche Standards als Handelshemmnisse betrachtet. Deshalb fordert man die Harmonisierung der divergierenden Standards - und nicht deren Konkurrenz - und/oder die Entwicklung neuer internationaler Standards. Nur Standards, die von offiziellen Organisationen verabschiedet wurden, werden anerkannt. Private Organisationen und die von ihnen erarbeiteten Standards werden hingegen tendenziell ignoriert.
Keywords: F02; L96; F13; 330; International Economic Order; Trade Negotiations; Technical Standards; Telecommunications; Telekommunikation; Normung; Internationale Handelspolitik; WTO-Regeln; Institutioneller Wettbewerb; Nichttarifäre Handelshemmnisse; Welt